Mixed methods study of clinicians’ perspectives on barriers to implementation of treat to target in psoriatic arthritis - Dures, E; Taylor, J; Shepperd, S; Mukherjee, S; Robson, J; Vlaev, I; Walsh, N; Coates, LC (BMJ Publishing Group, 2020)
Objectives In treat to target (T2T), the patient is treated to reach and maintain specified and sequentially measured goals, such as remission or low disease activity. T2T in psoriatic arthritis (PsA) has demonstrated improved clinical and patient-reported outcomes and is recommended in European guidelines. However, most clinicians do not use T2T in PsA. This study examined the barriers and enablers to implementation in practice.